EU action to protect women's rights in the Philippines - Czapla, Karolina (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
The Philippines takes the global issue of discrimination against women seriously and stands out among other countries in the Southeast Asian region for its approach to protecting women's rights and gender equality. However, many Filipinas still fall victim to domestic violence, human trafficking, and discrimination. The European Union has been assisting the Philippine authorities in combating these issues for years. The aim of this chapter is to present the situation of women in the Philippines and the actions taken by the European Union to protect women's rights. The chapter analyzes the socio-legal context and the role of women in the Philippines, EU strategies for protecting women's rights, as well as EU projects and initiatives carried out in this regard in the Philippines. This allows addressing questions regarding the situation of Filipino women, EU actions for their protection, and the obstacles to achieving gender equality in the Philippines.